Exploring associations between self-regulatory mechanisms and neuropsychological functioning and driver behaviour after brain injury. Issue 3 (3rd April 2018) - Rike, Per-Ola; Johansen, Hans J.; Ulleberg, Pål; Lundqvist, Anna; Schanke, Anne-Kristine
ABSTRACT: The objective of this prospective one-year follow-up study was to explore the associations between self-regulatory mechanisms and neuropsychological tests as well as baseline and follow-up ratings of driver behaviour. The participants were a cohort of subjects with stroke and traumatic brain injury (TBI) who were found fit to drive after a multi-disciplinary driver assessment (baseline). Baseline measures included neuropsychological tests and ratings of self-regulatory mechanisms, i.e., executive functions (Behavior Rating Inventory of Executive Function–Adult Version; BRIEF-A) and impulsive personality traits (UPPS Impulsive Behavior Scale). The participants rated pre-injury driving behaviour on the Driver Behaviour Qestionnaire (DBQ) retrospectively at baseline and after one year of post-injury driving (follow-up). Better performance on neuropsychological tests was significantly associated with more post-injury DBQ Violations. The BRIEF-A main indexes were significantly associated with baseline and follow-up ratings of DBQ Mistakes and follow-up DBQ Inattention. UPPS (lack of) Perseverance was significantly associated with baseline DBQ Inattention, whereas UPPS Urgency was significantly associated with baseline DBQ Inexperience and post-injury DBQ Mistakes. There were no significant changes in DBQ ratings from baseline (pre-injury) to follow-up (post-injury). It was concluded that neuropsychological functioning and self-regulatory mechanisms are related to driver behaviour. Some aspects of driver behaviour do not necessarily change after brain injury, reflecting the influence of premorbid driving behaviour or impaired awareness of deficits on post-injury driving behaviour. Further evidence is required to predict the role of self-regulatory mechanisms on driver behaviour and crashes or near misses.